Design and optimization of a SiC thermal emitter/absorber composed of periodic microstructures based on a non-linear method - 王卫杰 赵振国 赵艺 周海京 符策基 (Chinese physics B, 2015)
Spectral and directional control of thermal emission based on excitation of confined electromagnetic resonant modes paves a viable way for the design and construction of microscale thermal emitters/absorbers. In this paper, we present numerical simulation results of the thermal radiative properties of a silicon carbide（Si C） thermal emitter/absorber composed of periodic microstructures. We illustrate different electromagnetic resonant modes which can be excited with the structure,such as surface phonon polaritons, magnetic polaritons and photonic crystal modes, and the process of radiation spectrum optimization based on a non-linear optimization algorithm. We show that the spectral and directional control of thermal emission/absorption can be efficiently achieved by adjusting the geometrical parameters of the structure. Moreover, the optimized spectrum is insensitive to 3% dimension modification.